2022
DOI: 10.1021/acs.joc.2c01139
|View full text |Cite
|
Sign up to set email alerts
|

Radical Addition of Dihydroquinoxalin-2-ones to Trifluoromethyl Ketones under Visible-Light Photoredox Catalysis

Abstract: A visible-light photocatalytic radical addition reaction of dihydroquinoxalin-2-ones to trifluoromethyl ketones has been established using Ru(bpy) 3 Cl 2 as photocatalyst, acetonitrile as solvent, and HP Single Blue LED as the source of light. The reaction provides a straightforward approach to the synthesis of dihydroquinoxalin-2-ones bearing a trifluoromethyl-substituted tertiary alcohol moiety in moderate to good yields under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This easier oxidation of the reaction mixture ( 1 a + 2 a ) can be considered a proton‐coupled electron transfer (PCET), acting 1 a as a base. Upon studying the fluorescence quenching of the Fukuzumi catalyst, we also observed that adding a 1 : 1 mixture of 1 a / 2 a produced a much more pronounced effect than adding each reactant alone (Scheme 4g and page S34 in Supporting Information) [33] …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…This easier oxidation of the reaction mixture ( 1 a + 2 a ) can be considered a proton‐coupled electron transfer (PCET), acting 1 a as a base. Upon studying the fluorescence quenching of the Fukuzumi catalyst, we also observed that adding a 1 : 1 mixture of 1 a / 2 a produced a much more pronounced effect than adding each reactant alone (Scheme 4g and page S34 in Supporting Information) [33] …”
Section: Resultsmentioning
confidence: 88%
“…Upon studying the fluorescence quenching of the Fukuzumi catalyst, we also observed that adding a 1 : 1 mixture of 1 a/2 a produced a much more pronounced effect than adding each reactant alone (Scheme 4g and page S34 in Supporting Information). [33] Scheme 4. Mechanistic studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, radical sp 2 nucleophilic addition and radical–radical coupling via photoredox catalysis are great approaches to synthesize sterically hindered alcohols, in which photocatalysts, metal catalysts, strong bases and other additives are necessary, as well as organic solvent as the reaction medium. 6,7 These transformations usually involve the formation of C(sp 3 )–C(sp 3 ) bonds by highly reactive alkylates and carbonyl compounds (Fig. 1c.1).…”
mentioning
confidence: 99%
“…Despite these successful examples, these reports are limited to acyclic amines. As a part of our continuing interest in the development of synthetic approaches for the generation of α-amino radicals from other tertiary amines such as 3,4-dihydroquinoxalin-2-ones, we envisioned that these cyclic amines could be suitable α-amino radical precursors which undergo a 1,6-radical addition with para -quinone methides using photocatalysis (Scheme ). Furthermore, 1,4-dihydroquinoxalinones are an interesting class of nitrogen heterocycles which are present in many molecules with biological activities such as antiviral, anticancer or anti-inflammatory compounds .…”
mentioning
confidence: 99%